Artificial Intelligence and the Enhancement of Shariah Transparency in Islamic Finance: A Contemporary Jurisprudential-Economic Vision - سعدالله فريال رشيد علي; المشهداني رمضان محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Islamic finance is witnessing significant development across the world, yet its institutions still face challenges related to transparency and actual compliance with Shariah regulations, especially given the complexity of modern financial products. This research aims to examine the potential of employing artificial intelligence (AI) technologies as a modern Shariah oversight tool. This tool contributes to enhancing transparency and compliance within Islamic financial institutions by developing intelligent algorithms that mimic the principles of Islamic jurisprudence (fiqh) and the objectives of Shariah (Shariah) to verify the integrity of contracts and transactions such as sukuk, murabaha, and musharaka. The research also examines the relationship between AI and the major objectives of Shariah (Shariah), such as achieving fairness, clarity, and preventing uncertainty. It proposes an applied model that can be adopted by Shariah supervisory boards of banks. The study relies on a comparative analytical approach to highlight the similarities and differences between traditional and modern digital oversight tools, while employing an inductive approach to review the most prominent international success stories in this field. The research highlights its importance in offering an innovative solution to the problem of limited oversight and establishing a contemporary Shariah oversight model that aligns with the requirements of the digital age, without compromising the essence of Shariah regulations. The study concluded that the integration of Islamic jurisprudence and artificial intelligence represents a qualitative shift in the governance of Islamic financial work and enhances community confidence in Islamic institutions, provided that this employment is carried out within a clear legal framework that ensures the preservation of privacy and the achievement of the objectives of Sharia.